Letter (copy) : Alberto Santo Tomas Rodriquez - Tewson, Vincent
038-0050-001 Secretary's. HVT/FC/EK/529. 11th January, 1940. Mr. G. Stolz, International Federation of Trade Unions, 9, Avenue D'Orsay, PARIS VIIe. Dear Mr. Stolz, ALBERTO SANTO TOMAS RODRIGUEZ. With reference to your letter of the 4th instant in regard to the above boy, we can find no trace of any child of that name having arrived in England. The children who came to England in the steamer " Habana " arrived in May 1937 - I believe it was on the 27th. This would make it almost impossible for the boy to have come to England if the date of sailing from Bilbao was the 12th June. Probably, therefore, he was taken to France. Yours sincerely, Assistant Secretary. 292/946/38/50